Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1985
DOI: 10.1042/bj2320781
|View full text |Cite
|
Sign up to set email alerts
|

Different forms of human liver glutathione s-transferases arise from dimeric combinations of at least four immunologically and functionally distinct subunits

Abstract: Four immunologically distinct subunits were characterized in glutathione (GSH) S-transferases of human liver. Five cationic enzymes (pI 8.9, 8.5, 8.3, 8.2 and 8.0) have an apparently similar subunit composition, and are dimers of 26 500-Mr (A) and 24 500-Mr (B) subunits. A neutral enzyme, pI 6.8, is a dimer of B-type subunits. One of the anionic enzymes, pI 5.5, is also a dimer of 26 500-Mr subunits. However, the 26 500-Mr subunits of this anionic enzyme form are immunologically distinct from the A subunits of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
2

Year Published

1986
1986
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 27 publications
3
32
2
Order By: Relevance
“…It is possible that the differences in the results could be due to the different experimental conditions. However, it has to be noted that the acidic GSH transferase of liver and placenta appears to be structurally different [29]. The lower affinity site for hemin found in the placental enzyme has a dissociation constant which is very similar to the value reported by Takikawa for the acidic human liver GSH transferase [18].…”
Section: Discussionsupporting
confidence: 54%
“…It is possible that the differences in the results could be due to the different experimental conditions. However, it has to be noted that the acidic GSH transferase of liver and placenta appears to be structurally different [29]. The lower affinity site for hemin found in the placental enzyme has a dissociation constant which is very similar to the value reported by Takikawa for the acidic human liver GSH transferase [18].…”
Section: Discussionsupporting
confidence: 54%
“…Neither Soma et al [ 14] nor Stockman et al [ 13] employed urea SDS-PAGE which we found to be a convenient method for identi fication of the subunit composition of the purified proteins. Our results along with these other two laboratories seem to be dif ferent from Singh et al [23] with respect to subunit composition of the human hepatic transferases.…”
Section: Discussioncontrasting
confidence: 67%
“…They found two subunits for forms 8 and e on urea SDS-PAGE. Further work by this group has suggested that five forms of cationic transferase resolved on iso electric focusing are all heterodimers [23], This suggestion has not been confirmed by others [this report, ref. 13,14].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…13 different forms of GST have been identified in human liver (13). These human isozymes are formed by different combinations of a t least four different subunits (13,29). The nomenclature applied to the rat has not, been used for man or other species, making comparison ofthe different enzymes difficult.…”
Section: Nomenclaturementioning
confidence: 99%